2017
DOI: 10.1039/c7ta01441d
|View full text |Cite
|
Sign up to set email alerts
|

The intrinsic properties of FA(1−x)MAxPbI3 perovskite single crystals

Abstract: We provided a systematical investigation to correlate the crystal structure, composition, mobility, and ion migration behavior to the ratio of MA+/FA+ in FA(1−x)MAxPbI3 single crystal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
122
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(131 citation statements)
references
References 41 publications
8
122
1
Order By: Relevance
“…The orbitals of the countercations do not significantly contribute to the frontier bands, but influence the perovskite lattice type, lattice constants, and structural stability. Other experimental approaches to short-term stabilization of α-FAPbI 3 (besides rapid thermal quenching) include doping of the material with MA, [22][23][24][25] Cs, [26,27] and both MA and Cs, [28][29][30] but not with organic cations that bond stronger to the inorganic skeleton than FA. The higher the degree of covalent conjugation, the lower is the bandgap, the larger are radii of the excitons, the lower are the exciton binding energies, and, finally, the more efficient is the charge carrier transport in the material.…”
Section: Introductionmentioning
confidence: 99%
“…The orbitals of the countercations do not significantly contribute to the frontier bands, but influence the perovskite lattice type, lattice constants, and structural stability. Other experimental approaches to short-term stabilization of α-FAPbI 3 (besides rapid thermal quenching) include doping of the material with MA, [22][23][24][25] Cs, [26,27] and both MA and Cs, [28][29][30] but not with organic cations that bond stronger to the inorganic skeleton than FA. The higher the degree of covalent conjugation, the lower is the bandgap, the larger are radii of the excitons, the lower are the exciton binding energies, and, finally, the more efficient is the charge carrier transport in the material.…”
Section: Introductionmentioning
confidence: 99%
“…23,25 The phase stability of MA 1Àx FA x PbI 3 has been studied for samples stored under a nitrogen atmosphere, indicating that for FA-rich compositions with x > 0.76, partial transition to the hexagonal phase is observed within days, while for compositions with more MA, the hexagonal phase is not observed by X-ray diffraction. 30 The propensity for hybrid perovskites to react with water has also been reported.…”
mentioning
confidence: 99%
“…[22][23][24][25] We have previously shown that for compositions MA 1Àx FA x PbI 3 0 < x < 0.2 the structures are best described by a tetragonal unit cell from X-ray diffraction, while the rest of the composition range, 0.2 # x # 1, forms with a cubic cell, space group Pm 3m.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The shapes of the MHP SCs can be controlled by choosing the geometry of the vessel in which crystallization occurs. SCs based on other MHPs, such as MAPbX 3 , FAPbX 3 , and FA 1− x MA x PbX 3 , can be synthesized using ITC.…”
Section: Single Crystals and Light‐emitting Diodesmentioning
confidence: 99%